Eriodictyol Attenuates MCAO-Induced Brain Injury and Neurological Deficits via Reversing the Autophagy Dysfunction - Wang, Chuanxiang; Ma, Zhequan; Wang, Zuqiang; Ming, Shuping; Ding, Yanbing; Zhou, Sufang; Qian, Hongyu (Frontiers in Systems Neuroscience, 2021)
The present study was designed to investigate the protective effect of eriodictyol on MCAO-induced brain injury and its regulation of neural function and to explore the mechanism of its regulation of autophagy in rats. Brain injury was induced by middle cerebral artery occlusion (MCAO) in adult rats and pretreated with eriodictyol (low dose: 20 mg/kg; medium dose: 40 mg/kg; high dose: 80 mg/kg) or saline. Rats in the treatment group had a smaller volume of infarction and improved neurological outcome and reduced the latency to the platform, increased the time spent in the correct quadrant compared to MCAO rats pretreated with saline. ELISA kits results confirmed that eriodictyol reduced the inflammatory response induced by MCAO. The results of apoptosis and proliferation by Nissl staining and immunofluorescence detection indicated that eriodictyol could inhibit apoptosis and promote the proliferation in MCAO rats. The expressions of LC3, ATG5, p62, and Beclin1 were used to evaluate the autophagy, as well as the reversal of the autophagy activator (rapamycin) on the neuroprotective effect of eriodictyol, which suggested the protective effect of eriodictyol on brain injury may be related to the inhibition of autophagy. In summary, we, therefore, suggested that eriodictyol could reduce the inflammation response of brain injury and inhibit neuroapoptosis, directly affecting autophagy to alleviate brain injury. It will provide theoretical support for eriodictyol in the treatment of ischemic stroke. Keywords: Eriodictyol; Autophagy; Middle cerebral artery occlusion (MCAO); Inflammation; Apoptosis